2020
DOI: 10.1021/acsaem.0c02222
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Palladium Nanoparticles Stabilized in the Porous Liquid of Covalent Organic Cages for Photocatalytic Hydrogen Evolution

Abstract: Soluble covalent organic cages (COCs) were designed to comprise cryptand inner cavities and multiple metal-chelating sites on windows. The porous liquid formed by well-dispersed COCs in solution proves to be an excellent stabilizer for ultrafine palladium nanoparticles with a critical size of 1–3 nm using NaBH4 or methanol as a reductant. When transferring palladium nanoparticles stabilized in the porous liquid of COCs onto carbon nitride (g-C3N4), an efficient heterogeneous photocatalyst could be obtained to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…More recently, Pan et al have also demonstrated the catalysis application using PLs. [64] They synthesized a series of covalent Hollow silica (HS) PL Supported HS-liquid membrane organic cages (COCs)-based PLs with varied cryptand inner cavities and metal chelating sites on windows. The stabilized and well-dispersed PdNPs within PLs were combined with g-C 3 N 4 .…”
Section: Catalytic Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Pan et al have also demonstrated the catalysis application using PLs. [64] They synthesized a series of covalent Hollow silica (HS) PL Supported HS-liquid membrane organic cages (COCs)-based PLs with varied cryptand inner cavities and metal chelating sites on windows. The stabilized and well-dispersed PdNPs within PLs were combined with g-C 3 N 4 .…”
Section: Catalytic Conversionmentioning
confidence: 99%
“…d) Schematic illustration of the formation and stabilization of PdNPs in C 4 R COCs PL for photocatalytic hydrogen evolution. (Reproduced with permission [64]. Copyright 2020, American Chemical Society).…”
mentioning
confidence: 99%
“…[9][10][11] Unfortunately, such tiny MNPs with high surfaceenergy are thermodynamically unstable and prone to agglomerate and coalescence during catalysis reactions, resulting in a dramatic decrease in catalytic activity, thus limiting their practical applications. [12][13][14] To address this issue, encapsulating metal species into porous materials, such as metal-organic frameworks, [15][16][17][18][19][20] covalent-organic frameworks, [21][22][23] and organic cages, [24][25][26][27][28][29][30][31][32][33] has been demonstrated to be a powerful strategy to engineer the controlled synthesis and stabilization of ultrane MNPs. However, the synthesis of such ultrane MNPs with a narrow size distribution and high stability is still a big challenge.…”
Section: Introductionmentioning
confidence: 99%
“…41 Furthermore, the performance of Pd doped RCC3 cage toward semi-hydrogenation of alkyne and hydrogenation of 4-nitrophenol compounds was demonstrated both experimentally and theoretically by Kou et al 42 Covalent organic cages (COCs) are also reported with high catalytic efficiency for hydrogen evolution reaction (HER). 43…”
Section: Introductionmentioning
confidence: 99%